The influence of nano-additives on the technical properties of drilling mud for drilling and well reconstruction - A.Y. Abusal Yousef; Irina A. Chetvertneva; Rustem A. Ismakov; Artur R. Yakhin; Marianna E. Loginova (Нанотехнологии в строительстве)
Introduction. Drilling and reconstruction of oil and gas wells are key stages in the development of hydrocarbon fields. One of the most significant technological elements that greatly influences the efficiency of the process is the drilling fluid (DF). It performs many functions, including cooling and lubrication of rock-cutting and special tools, bottomhole cleaning from drilled rock, maintaining well wall stability and many others. In recent years, special attention has been paid to the use of nanomaterials in the DF drilling fluid composition. Nanoscale additives can significantly improve technological properties of water-based muds, increase their efficiency and reduce drilling costs. Methods and Materials. The influence of additives on general technological parameters of Clay-Free Drilling Mud (CFDM) was evaluated. Special attention was paid to revealing the influence of the developed experimental additives on the friction coefficient and antifriction properties of (CFDM), which were determined using modified friction machine AI5018. Results and discussion. This study focuses on the investigation of the impact of nano-additives on the technical properties of water-based mud (WBs) and their effectiveness for drilling and well reconstruction. In the course of the work, comprehensive laboratory studies have been carried out to evaluate the effect of nano-additives of different nature, such as nano-graphite and nano-carbon materials, on the lubricating properties of water-based mud (WBs), which helps to reduce the wear of drilling equipment, increase the mechanical speed of drilling and, as a consequence, reduce the time and financial costs of well construction and re-construction. Conclusion. The introduction of nano-additives allowed significantly in improving the technological properties of drilling fluid DF. The obtained results can be used to improve the compositions of solutions based on the use of nanomaterials, which will increase the efficiency and reliability of well drilling processes